CAUSALITY RELATIONSHIP OF FINANCING, POVERTY, UNEMPLOYMENT, CONSUMER PRICE INDEX AND ECONOMIC GROWTH IN INDONESIA - Muhammad Nasir; Lianti Lianti; Muhammad Syuib; Hamdani Hamdani; Safaruddin Safaruddin (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of financing and unemployment on economic growth in Indonesia. This study was conducted in 33 provinces over a period of 7 years from 2011-2017. The data analysis tool used is the Vector Error Correction Model (VECM) panel. These results prove that all variables such as financing, poverty, unemployment and the consumer price index have an effect on economic growth in Indonesia. There is sufficient evidence that financing, poverty, unemployment and the consumer price index are closely related to economic growth. The recommendation from this research is that Islamic banking can increase financing as an effort to improve the economy. As for the government, they are urged to control the level of poverty and unemployment.